Improving Understanding of In Vitro Plant Propagation by Plant Study Community through Plant Tissue Culture Workshop - Rizal Koen Asharo; Raisyanggi Susta Mulyadi; Fadya Hidayatie; Farhana Faridah Achmad; Karina; Firdaus Zakirin Maspar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract This community service program aims to improve the understanding and skills of the Plant Study Community in in vitro plant propagation techniques through tissue culture workshop. This activity is motivated by the importance of tissue culture technology in multiplying plants quickly, disease-free, and with superior genetic quality. The training includes theory and direct practice, including explant sterilization, propagation through culture media, and acclimatization of culture results in an open environment. Training participants gain in-depth knowledge of tissue culture techniques and their applications in modern agriculture, as well as their ability to support the conservation and recovery of rare plant species. The results of this program show a significant increase in participants^ theoretical understanding and practical skills, which are expected to contribute to the application of this technology at the community and education levels. Keywords: plant tissue culture, plant propagation, in vitro, training, plant conservation Abstrak Program pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pemahaman dan keterampilan Komunitas Studi Tanaman dalam teknik perbanyakan tanaman in vitro melalui workshop kultur jaringan. Kegiatan ini dilatarbelakangi oleh pentingnya teknologi kultur jaringan dalam memperbanyak tanaman dengan cepat, bebas penyakit, dan dengan kualitas genetik yang unggul. Pelatihan meliputi teori dan praktik langsung, termasuk sterilisasi eksplant, perbanyakan melalui media kultur, dan aklimatisasi hasil kultur di lingkungan terbuka. Peserta pelatihan mendapatkan pengetahuan mendalam tentang teknik kultur jaringan dan aplikasinya dalam pertanian modern, serta kemampuan mereka untuk mendukung konservasi dan pemulihan spesies tanaman langka. Hasil program ini menunjukkan peningkatan yang signifikan dalam pemahaman teoritis dan keterampilan praktis peserta^, yang diharapkan dapat berkontribusi pada penerapan teknologi ini di tingkat masyarakat dan pendidikan. Kata Kunci: kultur jaringan tanaman, perbanyakan tanaman, in vitro,, pelatihan, konservasi tanaman